Safety and efficacy of peramivir for influenza treatment - Hata A; Akashi-Ueda R; Takamatsu K; Matsumura T (Dove Medical Press, 2014)
Atsuko Hata,1,2 Ryoko Akashi-Ueda,1 Kazufumi Takamatsu,3 Takuro Matsumura2 1Department of Pediatrics, 2Department of Infectious Diseases, 3Respiratory Disease Center, Division of Respiratory Medicine, Kitano Hospital, The Tazuke Kofukai Medical Research Institute, Osaka, Japan Objective: This report presents a review of the efficacy and safety of peramivir, a neuraminidase inhibitor that was granted Emergency Use Authorization by the US Food and Drug Administration (FDA) from October 23, 2009 to June 23, 2010 during the 2009 H1N1 pandemic.Methods: Literature was accessed via PubMed (January 2000–April 2014) using several search terms: peramivir; BCX-1812; RWJ 270201; H1N1, influenza; antivirals; and neuraminidase inhibitors. The peramivir manufacturers, Shionogi and Co Ltd and BioCryst Pharmaceuticals, were contacted to obtain unpublished data and information presented at recent scientific meetings. Information was obtained from the Centers for Disease Control and Prevention (CDC) and from US FDA websites. English-language and Japanese-language reports in the literature were reviewed and selected based on relevance, along with information from the CDC, US FDA, and the drug manufacturers.Results: We obtained eleven clinical trial reports of intravenous peramivir, two of which described comparisons with oseltamivir. Seven of nine other recently reported published studies was a dose–response study. Clinical reports of critically ill patients and pediatric patients infected with pandemic H1N1 described that early treatment significantly decreased mortality. Peramivir administered at 300 mg once daily in adult patients with influenza significantly reduces the time to alleviation of symptoms or fever compared to placebo. It is likely to be as effective as other neuraminidase inhibitors.Conclusion: Although peramivir shows efficacy for the treatment of seasonal and pH1N1 influenza, it has not received US FDA approval. Peramivir is used safely and efficiently in hospitalized adult and pediatric patients with suspected or laboratory-confirmed influenza. Peramivir might be a beneficial alternative antiviral treatment for many patients, including those unable to receive inhaled or oral neuraminidase inhibitors, or those requiring nonintravenous drug delivery. Keywords: neuraminidase inhibitor, pandemic, pH1N1, avian flu, antiviral therapy, drug resistance